Characterization of holmium(iii)-acetylacetonate complexes derived from therapeutic microspheres by infrared ion spectroscopy. Issue 27 (3rd July 2020) - Houthuijs, Kas J.; Martens, Jonathan; Arranja, Alexandra G.; Berden, Giel; Nijsen, J. Frank W.; Oomens, Jos
Abstract : Microspheres containing holmium radionuclides and acetylacetonate are novel anti-tumour agents in cancer therapies. We employ infrared ion spectroscopy to analyze the composition and coordination geometries of the species detected in dissolved microspheres. Abstract : Microspheres containing radioactive 166 holmium-acetylacetonate are employed in emerging radionuclide therapies for the treatment of malignancies. At the molecular level, details on the coordination geometries of the Ho complexes are however elusive. Infrared ion spectroscopy (IRIS) was used to characterize several 165 Ho-acetylacetonate complexes derived from non-radioactive microspheres. The coordination geometry of four distinct ionic complexes were fully assigned by comparison of their measured IR spectra with spectra calculated at the density functional theory (DFT) level. The coordination of each acetylacetonate ligand is dependent on the presence of other ligands, revealing an asymmetric chelation motif in some of the complexes. A fifth, previously unknown constituent of the microspheres was identified as a coordination complex containing an acetic acid ligand. These results pave the way for IRIS-based identification of microsphere constituents upon neutron activation of the metal center.